Penggunaan Resistivity Meter Berbasis Boost converter Untuk Identifikasi Batuan Dasar Pancang Pondasi Bangunan di Pulau Tarakan - Muis Prasetia, Abdul; Aidil, Rachmad; Faizal, Rahmat (Borneo Engineering : Jurnal Teknik Sipil, 2018)
The strength of the building foundation is strongly influenced by the type of soil layer that used as a foundation laying place. The higher the building to be built, the stronger the foundation to be made. This research was conducted to identify the bedrock of the existing soil layer in Tarakan City by using a boost converter-based resistivity meter with aim to minimize the impact of building damage caused by soil structure. Boost converter is a step-up DC-DC converter. Boost converter is able to produce an output voltage value greater than the input voltage without the need of transformer. The boost converter design is started by determining parameter based on the needs of resistivity meter. Resistivity data acquisition has been conducted at several points in Universitas Borneo Tarakan by using the Schlumberger configuration. Data processing has been done by using a matching curve. The results of the interpretation of the processing of geoelectric data are 4 soil layers with a depth of 12 meters. In the geoelectric estimation investigation area has a type of resistance between 6.08 -169.79 Ohm-meters. The layer that is expected to act as a bedrock is sand at a depth of 13.81 meters and sandstone sand at a depth of ± 8 meters, with these conditions, the construction of a foundation for the construction of lightweight buildings can already be built